Ideal Points and American Political Development: Beyond DW-NOMINATE. Issue 2 (5th July 2016) - Bateman, David A.; Lapinski, John
Abstract : This article aims to persuade historically oriented political scientists that ideal point techniques such as DW-NOMINATE can illuminate much about politics and lawmaking and be very useful to better understanding some of the key questions put forward by American political development (APD) scholars. We believe that there are many lines of inquiry of interest to APD scholars where ideal point measure could be useful, but which have been effectively foreclosed because of the assumptions undergirding DW-NOMINATE. In particular, we focus on three issues as particularly important: (1) the assumption of linear change; (2) the collapsing of distinct policy issue areas into a single "ideology" score; and (3) an agnosticism toward policy development, institutional context, and historical periodization. We go over these issues in detail and propose that many of these concerns can be addressed by taking seriously the proposition that policy substance, historical and political context, and the temporal dimension of political processes be integrated into the core of our measures and analyses. We also discuss a set of techniques for addressing these issues in order to answer specific questions of broad interest to both APD scholars and other Americanists.